2015
DOI: 10.1063/1674-0068/28/cjcp1411201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxylamine Sulfate and Sodium Nitrite on Microstructure and Friction Behavior of Zinc Phosphating Coating on High Carbon Steel

Abstract: Hydroxylamine sulfate (HAS) and sodium nitrite are used as the accelerators for zinc phosphate coating on high carbon steel. Phase evolution of phosphate coating was investigated by X-ray diffraction. It is found that the phosphating coatings are mainly composed of hopeite Zn 3 Fe(PO 4) 2 •4H 2 O and phosphophyllite Zn 2 Fe(PO 4) 2 •4H 2 O. The microstructural changes of the phosphate coating, as a function of phosphating time, were evaluated by scanning electron microscopy. Four-ball friction experiments reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Generally, for the preparation of chemical conversion surface films, the category of additive in surfactants plays an important role, and their inhibiting effect on corrosion development has been widely studied [8]. Generally, the main functions of additives consist of the following: (1) promoting the formation of a coating film; (2) reducing particle crystallinity; (3) controlling the conversion rate; (4) increasing the hydrophobicity of the metal surface; and (5) enhancing the solubility of the main components of the conversion fluid in water [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, for the preparation of chemical conversion surface films, the category of additive in surfactants plays an important role, and their inhibiting effect on corrosion development has been widely studied [8]. Generally, the main functions of additives consist of the following: (1) promoting the formation of a coating film; (2) reducing particle crystallinity; (3) controlling the conversion rate; (4) increasing the hydrophobicity of the metal surface; and (5) enhancing the solubility of the main components of the conversion fluid in water [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…(2) reducing particle crystallinity; (3) controlling conversion rate; (4) increasing hydrophobicity of the metal surface and 5) enhancing the solubility of the main components of the conversion fluid in water [41][42][43][44][45][46][47][48][49][50][51][52]. Cui et al [43] reported the influence of the added Mn(NO 3 ) 2 and Na 2 MoO 4 on the phosphate conversion coatings on the surface of AZ31B alloy and found that the corrosion protectability of phosphate conversion coatings with additives was significantly improved because the particle size of phosphate conversion coatings was significantly decreased with the addition of Na 2 MoO 4 .…”
Section: Introductionmentioning
confidence: 99%